The Hamilton-Jacobi Treatment of Complex Fields as Constrained Systems - Tamer Eleyan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The complex scalar field is treated as a constrained system using the Hamilton-Jacobi approach. The reduced phase space Hamiltonian density is obtained without introducing Lagrange multipliers and without any additional gauge fixing condition. The quantization of this system is also discussed.